2020
DOI: 10.1002/jha2.122
|View full text |Cite
|
Sign up to set email alerts
|

Selinexor, daratumumab, and dexamethasone in patients with relapsed or refractory multiple myeloma

Abstract: We assessed the safety, efficacy, maximum tolerated dose (MTD), and the recommended phase 2 dose (RP2D) of selinexor, a first in class oral selective inhibitor of nuclear export (100 mg once weekly [QW] or 60 mg twice weekly), in combination with daratumumab (16 mg/kg per label) and dexamethasone (40 mg QW) (SDd) in patients with relapsed refractory multiple myeloma (RRMM). Thirty‐four patients (median prior therapies, 3 [range, 2‐10]) were enrolled; MM was refractory to proteasome inhibitor (PI) in 85%, immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Specifically, high-risk MM is characterized by the presence of gain of chromosome 1q, deletion of chromosome 17p (del(17p)), t(4;14), t(14;16), t(14;20) or p53 mutations [ 9 , 12 ]. Despite therapeutic advances including the introduction of ImmunoModulatory Drugs (IMiDs), proteasome inhibitors (PIs), monoclonal antibodies and most recently selinexor, a Selective Inhibitor of Nuclear Export (SINE) that binds and inactivates exportin-1 (XPO1) [ 13 ], the B Cell Maturation Antigen (BCMA) targeting antibody-drug-conjugate (ADC) belantamab-mafodotin [ 14 ], and BCMA-directed CAR-T cells [ 9 ], the management of MM remains challenging, mainly due to the development of drug resistance. Therefore, the identification of novel therapeutic targets and the development of derived anti-MM treatment strategies are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, high-risk MM is characterized by the presence of gain of chromosome 1q, deletion of chromosome 17p (del(17p)), t(4;14), t(14;16), t(14;20) or p53 mutations [ 9 , 12 ]. Despite therapeutic advances including the introduction of ImmunoModulatory Drugs (IMiDs), proteasome inhibitors (PIs), monoclonal antibodies and most recently selinexor, a Selective Inhibitor of Nuclear Export (SINE) that binds and inactivates exportin-1 (XPO1) [ 13 ], the B Cell Maturation Antigen (BCMA) targeting antibody-drug-conjugate (ADC) belantamab-mafodotin [ 14 ], and BCMA-directed CAR-T cells [ 9 ], the management of MM remains challenging, mainly due to the development of drug resistance. Therefore, the identification of novel therapeutic targets and the development of derived anti-MM treatment strategies are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…These triple-class refractory patients benefit from newly approved drugs with novel mechanism of action such as selinexor, which inhibits XPO-1-mediated nuclear export [55], or the immunoconjugate belantamab mafodotin (see next section) [56]. One study with 34 patients (median of three prior lines of therapy) showed that selinexor can also be effectively combined with daratumumab and dexamethasone [57]. Common adverse events with this IMiD-and PI-free regimen included thrombocytopenia, nausea, and fatigue.…”
Section: Triple-class Refractory Myelomamentioning
confidence: 99%
“…Selinexor, in combination with daratumumab and dexamethasone, has been evaluated, within the STOMP trial (NCT02343042), in 34 RRMM patients who had received three or more prior lines of therapy, including a PI and an IMiD, or whose MM was refractory to a PI and an IMiD ( 75 ). The median number of prior therapies was 3 (range: 2–10).…”
Section: Selinexormentioning
confidence: 99%
“…Selinexor (once weekly: 100 mg; twice weekly: 60 mg) in 28-day cycles; Daratumumab (16 mg/kg weekly for weeks 1-8, every 2 weeks for weeks 9-24, then every 4 weeks for weeks ≥25); Dexamethasone (40 mg once weekly) RP2D: Selinexor (100 mg once weekly), Daratumumab (16 mg/kg weekly for weeks 1-8, every 2 weeks for weeks 9-24, then every 4 weeks for weeks ≥25), Dexamethasone (40 mg once weekly) whose MM was refractory to a PI and an IMiD (75). The median number of prior therapies was 3 (range: 2-10).…”
Section: Ib/ii 34mentioning
confidence: 99%